2021
DOI: 10.1111/jns.12477
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal and cross‐sectional study of plasma neurofilament light chain concentration in Charcot‐Marie‐Tooth disease

Abstract: Advances in genetic technology and small molecule drug development have paved the way for clinical trials in Charcot‐Marie‐Tooth disease (CMT); however, the current FDA‐approved clinical trial outcome measures are insensitive to detect a meaningful clinical response. There is, therefore, a need to identify sensitive outcome measures or clinically relevant biomarkers. The aim of this study was to further evaluate plasma neurofilament light chain (NFL) as a disease biomarker in CMT. Plasma NFL was measured using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 37 publications
(75 reference statements)
3
33
2
Order By: Relevance
“…Responsiveness of these translatable biomarkers is highly encouraging for their utility in parallel clinical trials of miRNA therapies. Although, a recent study (79) showed a lack of correlation of NF-L plasma levels with disease progression over time in patients with CMT1A, this might be due to the older age of the patients tested (mean age, 46 years). In this regard, validation of additional clinically relevant plasma and skin biomarkers as indicators for future gene therapy efficacy would be essential (19,111,112,113).…”
Section: Discussionmentioning
confidence: 87%
“…Responsiveness of these translatable biomarkers is highly encouraging for their utility in parallel clinical trials of miRNA therapies. Although, a recent study (79) showed a lack of correlation of NF-L plasma levels with disease progression over time in patients with CMT1A, this might be due to the older age of the patients tested (mean age, 46 years). In this regard, validation of additional clinically relevant plasma and skin biomarkers as indicators for future gene therapy efficacy would be essential (19,111,112,113).…”
Section: Discussionmentioning
confidence: 87%
“…40 The demonstration of significantly increased plasma NFL in patients with CMT1A, and CMT1B has been replicated by other groups, 43,4441 ; however, the correlation between plasma NFL and the CMT neuropathy and examination scores has been replicated in some but not all studies. 40,41,43 In the only longitudinal study of plasma NFL in CMT, there was no significant change over 6 years follow-up period. 41 Subgroup analysis revealed a trend towards a reduction in plasma NFL over time in CMT1A and a significant reduction in CMT1X.…”
Section: Charcot-marie-tooth Diseasementioning
confidence: 88%
“…31 Subsequent studies using a more sensitive SIMOA platform measuring NFL have shown a significant albeit small difference (10 pg/ml compared to 51.3 pg/ml in ATTR amyloidosis) in patients with CMT (both axonal and demyelinating) versus controls. 37,[40][41][42][43] Subgroup analyses have shown significant NFL increases in the CMT1A, CMT1X and hereditary sensory neuropathy cohorts. 40 Encouragingly, there was also a significant correlation between plasma NFL and the clinical outcome measure, the CMT examination score version 2.…”
Section: Charcot-marie-tooth Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…36 These age-related changes are an important challenge when considering how to use the test clinically, resulting in the development of age-specific cut-points. It is also relevant that a number of common pathologies can elevate NfL, including mild traumatic brain injury, 37 cerebrovascular insults, 38 peripheral neuropathy 39 and kidney dysfunction, 40 all of which may need to be taken into account.…”
Section: B Lood B I Omark Er S For Neurodeg Ener Ationmentioning
confidence: 99%